Students’ Motivations for using Facebook for Academic Purposes: Qualitative Approach - Alwreikat, Asma (Dirasat: Human and Social Sciences, 2023)
Social media is a tool of communication, and the number of undergraduate students using Facebook is increasing. This study aims to identify the motivations for using Facebook by LIS students in Jordanian universities. The study deployed a thematic analysis approach that best identifies motivations in this context. The data collection tool is semi-structured interviews. 40 students were interviewed. The findings revealed four themes; Facebook facilitates studying, Facebook is a source of academic information, Facebook eases involvement in university activities and it is a source of communication. The implications of this research would help higher education institutions to develop strategies for incorporating social media use within traditional learning and E-learning process. Limitations and recommendations were presented at the end of the study.